Association of physical abilities and physiological characteristics with competitive efficacy of U16 female basketball players - Zaric, I.; Markovic, M.; Copic, N.; Kukic, F. (Serbian Journal of Sports Sciences, 2021)
This study investigated the association of physical abilities and physiological characteristics with competitive performance of female basketball players under 16 years of age (U16). The sample included 30 players from the three best basketball clubs in U16 league of Serbia (age = 14.98±0.68 years). Their maximal contractile force (Fmax) and rate of force development (RFDmax) of leg and back extensors and finger flexors were assessed via maximal isometric leg press, dead lift, and handgrip. Their maximal strength of leg muscles was assessed by vertical counter movement jump and Abalakov vertical jump, while anaerobic power of legs with Lactate and heart rate characteristics were assessed using the 30-s Wingate test. Competitive basketball performance was evaluated via competency index calculated from the official statistics for each player. The association were statistically tested using the multiple regression analysis. The results revealed significant predictive value (R2 = 0.462, p = 0.017) of physical and physiological profile of players in predicting competitive performance. Physical abilities and physiological characteristics of U16 female basketball players could be modeled and used as reference values for screening purposes in process of managing the training program of young players and for the checkpoints in development of players from young age to professional level.